â€œAtmanirbhar Bharat, â€ â€œDual Circulationâ€ : Shared Internal Woes Post COVID-19 Open not Dissimilar Economic Paths for India and China - Gupta, Manoj (Prabandhan: Indian Journal of Management, 2021)
China and India have announced, in quick succession, new economic measures to steer their countries out of the economic morass the global COVID-19 pandemic has pushed them into. China calls it the â€œDual Circulationâ€ Strategy. India calls it the â€œAtmanirbhar Bharatâ€ Mission. Both turn to their domestic markets as the primary focus to boost consumption without significantly reducing their international trade commitments. This article picked up on the unique similarity of the two new economic models of the two countries with otherwise dissimilar approaches to economics and politics rounded off by a precipitous stand-off over a border dispute. The distinguishing features of both missions were explained in the contexts of both economies. The challenges the countries have to overcome while steering the economies in the new direction were examined. The research provided a contrast that merits further, critical studies : China, with a mighty middle class but with uncharacteristically low consumption, proposes to create conditions for augmenting the domestic spending power, using it as the booster dose for its economy, which would serve as the stepping stone for augmenting exports. India, already riding a wave of increased domestic consumption by the middle class, is intent on making it possible to indegenize manufacturing processes through technological upgradation in order to lower costs to boost internal consumption and increase exports.